Multidrug-resistant Infection Following Snakebite Envenoming - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Snake Bite Envenoming (SBE) is a major under-appreciated medical and public health problem causing significant mortality and morbidity, particularly among rural dwellers throughout the tropics. Occasionally, snakebite may lead to important complications such as amputation, blindness resulting from spitting cobra (Naja nigricollis) induced venom ophthalmia, foetal loss, wound infection, tetanus and scarring with potential for malignant transformation. Here, we report a case of a 13 year old student bitten by a snake whose bite site became infected with multidrug resistant Methicillin Resistant Staphylococcus aureus (MRSA). He was bitten on the neck, in the night while sleeping on his bed. The bite site suppurated, the skin underwent necrosis and began to discharge thick brownish pus necessitating surgical exploration to drain deep-seated abscesses. The patient survived the acute phase after receiving intravenous polyvalent anti-snake venom (EchiTab-Plus(R)) and intravenous Levofloxacin in addition to wound care. The case stresses the need for comprehensive care of victims of snakebite. This care should be multidisciplinary, and health care workers should be educated on snakebite wound care and management.